Konsep Demokrasi Islam Dalam Pandangan Kuntowijoyo (Studi Pada Sejarah Peradaban Islam) - M. Sirajudin Fikri; Abdur Razzaq (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
Kuntowijoyo , trying to offer a concept of democracy which is based on the values contained in the Qur'an and Hadisth . Kunto provide rules contained in Islam which can be connected into the teachings of Islam . Kuntowijoyo used epistemological analysis of democracy and related it to the political dynamics of contemporary Indonesia. On one hand, Kunto accepted the concept of Western version of democracy , on the other hand Kunto gave a